PENGARUH MEKANISME CORPORATE GOVERNANCE DAN FIRM SIZE TERHADAP KONDISI FINANCIAL DISTRESS PADA PERUSAHAAN PROPERTY AND REAL ESTATE YANG TERDAFTAR DI BEI TAHUN 2010 - 2014 - LILI WARDANI HARAHAP (Jurnal Riset AKuntansi dan Bisnis, 2017)
The problems discussed in this study is the declining financial condition of the company's property and real estate in the year 2010-2014 due to bad corporate governance. The purpose of this study was to analyze the effect of corporate governance mechanism and firm size to the condition of financial distress. Corporate governance mechanism in this study include the institutional ownership, managerial ownership, director size, commissioner size, and audit committee size. This study used sample on property & real estate company which were listed on Indonesia Stock Exchange (IDX) during 2010-2014 period. Samples were taken by purposive sampling method. The samples used in this study are 159. The financial distress criteria in this study were measured by using Z-score on financial distress prediction models of Altman (1995). The data has analyzed by using multiple regression method. Keywords: Corporate governance, financial distress, institutional ownership,managerial ownership, director size, commissioner size, audit committee size, firm size.